Journalism and society - McQuail, Denis (London SAGE, 2013)
"This is a major new statement on the role of journalism in democracy from one of media and communication?s leading thinkers. Denis McQuail leads the reader through a systematic exploration of how and why journalism and society have become so inextricably entwined and - as importantly - what this relationship should be like. It is a strong re-statement of the fundamental values that journalism aspires to." -- Publisher website.
Preface -- What is journalism? How is it linked to society? -- Journalistic responsibility to society -- Principles of journalistic performance -- Towards a framework of analysis for journalism -- The central role of monitor and messenger -- Media structure, performance and the ?power of the press? -- The accountability of journalism to society -- Changing media technology : consequences for journalism, press institution and relations with society -- In conclusion : striking a normative balance -- Appendix : selected documents relating to rights and obligations of new media -- References -- Index.
Includes bibliographical references and index.
Keywords: Journalism -- Social aspects